Análisis jurídico y doctrinario de la sentencia no. 668-17- EP/22 de la Corte Constitucional por la retroactividad de normativa aplicable al cálculo de la jubilación patronal vulnerando la Seguridad Jurídica - Criollo Rojas, Bryan José (2024)
The present work of curricular integration entitled: "Legal and doctrinal analysis of the sentence No. 668-17-EP/22 of the Constitutional Court for the retroactivity of regulations applicable to the calculation of the employer's retirement in violation of the legal security", responds to the need to analyze and investigate based on the different criteria that exist concerning the application of retroactive regulations and in synthesis to the calculation of the retirement, responds to the need to analyze and investigate based on the different criteria that exist concerning the application of the retroactivity of regulations and in synthesis to the calculation of the retirement, since with the present investigation it has been possible to verify that there is a considered series of legal problems that have arisen from the non- clarification and the same non-observance of rules provided by the judges, in this way the right to legal certainty has been violated in principle. This analysis is intended to determine how retroactive application of the rule in the calculation of the employer's retirement in sentence 668-17/EP/2022 produces affectation and violation of rights to the worker and that the non-observance and omission of the rule by the administrators of justice violates basic principles of law, attempts against the dignified life of workers and above all does not guarantee fundamental rights that are the basis for ensuring an impartial, efficient and effective justice. Objective 16 of the Sustainable Development Plan establishes Peace, Justice, and Solid Institutions specifically anchored to this research topic refers to the facilitation of access to justice but is effective, efficient, and responsible this correlates with what is established in art. 82 of the CRE the respect for the rules provided and the guarantee of compliance by the competent authorities certainly in the obligation of judges to give faithful compliance and guarantees to the application of the Constitution, international instruments ratified by the State, and other rules and provisions that for the improvement of the judicial system have been implemented. With the present investigation, it is possible to determine that the retroactive application of the norm for the calculation of the employer's retirement in sentence 668/17-EP/2022 violates the rights of the worker and affects too much his life projection.